DEVELOPMENT OF ONLINE-BASED ENTREPRENEURIAL COMPETENCE ON PERFORMANCE BEHAVIOR IN SMALL AND MEDIUM ENTERPRISES - Azaluddin, Azaluddin; Ibanga, John; Mahmuda, Dewi; Sahida, Sahida (Faculty of Economics and Business, University of Pasundan, 2025)
A lack of technological understanding and limited assistance in applying acquired knowledge has caused many Small and Medium Enterprises (SMEs) to struggle in adopting modern and competitive business strategies. Therefore, this study aims to develop online-based entrepreneurial competencies and analyze their influence on performance behavior among SMEs in Baubau City. This research employs a mixed-methods approach combining quantitative and qualitative techniques supported by meta-analysis. Quantitative data were collected through questionnaires to obtain objective and measurable evidence of the relationship between online-based entrepreneurial competencies and SME performance behavior. Qualitative data were gathered through in-depth interviews to support and enrich the quantitative findings. In addition, meta-analysis was used to provide deeper insight into the consistency of findings from previous studies. The results show that online-based entrepreneurial competencies significantly improve SME performance behavior in Baubau City, despite limited individual digital effects.